Was the 1952 Tokachi‐oki earthquake (Mw= 8.1) a typical underthrust earthquake?: Plate interface reflectivity measurement by an air gun‐‐ocean bottom seismometer experiment in the Kuril Trench - Ryosuke Azuma; Yoshio Murai; Kei Katsumata; Yuichi Nishimura; Takuji Yamada; Kimihiro Mochizuki; Masanao Shinohara (Geochemistry, Geophysics, Geosystems, 2012)
The Kuril Trench subduction zone is one of the most seismogenic regions, where underthrust earthquakes with M> 8 recur along the trench. The seismic gap between the source areas of the 1973 Nemuro‐oki and 2003 Tokachi‐oki earthquakes, which are typical underthrust earthquakes faulting with rupture velocities of ∼3 km/s, has been ruptured by the 1952 Tokachi‐oki earthquake. The seismic gap has also slipped incidental to neighboring asperities. The difference in slip pattern on the plate interface generally appears as a spatial difference in seismic structure on the plate interface, such as a reflectivity of the plate interface. We estimated the crustal velocity structure and analyzed the reflectivity of the plate interface to investigate the physical properties of the plate interface by performing an air gun–ocean bottom seismometer experiment on the along‐trench profile across the seismic gap. Strong reflections from the plate interface were observed in the 1952 Tokachi‐oki source area including the seismic gap, rather than in the 1973 Nemuro‐oki source area. The strong reflectivity of the plate interface in such the seismic gap with an incidental slip suggests that a slip pattern in the corresponding seismic gap would be conditionally stable. The coupling condition in the source areas of the eastern part of the source area of the 1952 earthquake is different from that in source areas of typical underthrust earthquakes, such as the 2003 Tokachi‐oki and 1973 Nemuro‐oki earthquakes. Our results suggest that the 1952 Tokachi‐oki earthquake was a complex earthquake with the characteristic of a tsunami earthquake.